Understanding Turnover Culture in Organizations: A Literature Review - Padang, Bukti; Kasheem, Majdy (Malacca: Journal of Management and Business Development, 2024)
Employee turnover is a critical issue in human resource management, with significant implications for organizational performance, culture, and sustainability. This article explores the concept of turnover culture, defined as the shared beliefs, norms, and practices within an organization that influence employee retention or departure. Through a systematic review of literature from 2020 to 2024, this study identifies key factors contributing to turnover culture, including leadership styles, organizational climate, job satisfaction, and work-life balance. The findings highlight the importance of proactive HR strategies to mitigate turnover and foster a positive organizational culture. This article contributes to the growing body of knowledge on turnover culture by synthesizing recent research and offering practical recommendations for organizations.